A simulation structure for nursing education in mental health - Grochowska, Aneta; Kero, Johanna; Teeri, Sari; Alinen, Pauliina; Kołpa, Małgorzata; Cunnigham, Sheila; Lillo-Crespo, Manuel; Schembri, Neville; Abanifi, Phylis Farrugia; Pesonen, Hanna-Mari; Kukkola, Annukka; Prest, Anne; et al. (Health Promotion & Physical Activity, 2023)
The aim of the paper is to present a structure for nursing education simulation that incorporates elements of blended and online simulation in a socially constructivist, culturally sensitive environment. To develop the structure for nursing education, a descriptive literature review was conducted in spring 2022 on simulations implemented in mental health nursing education. Nurses require the skills and knowledge to provide mental health care in every area of health care. According to the descriptive literature review, simulation-based learning such as high-fidelity mental health simulation resulted in increased confidence, knowledge gains and improved communication skills. Simulation is a wide concept and allows nurse lecturers to implement the pedagogy as they see it best. The Simulation structure helps especially beginners to follow the simulation as a process. The structure eases the planning phase as well as the debriefing part of the simulation. As it has been shown in the analysis of the literature simulation can be effectively implemented in a blended and / or online environment. It is expected that in the future, simulation games and virtual, online simulations will be more typical ways to conduct a simulation.